State Legal Accountability for Alleged Genocide Against Rohingya Ethnic Group: Case Study of Myanmar Under the 1948 Genocide Convention - Silitonga, Marudut Parulian; Abdillah, Rachmat (Jurnal Indonesia Sosial Sains, 2025)
This study examines state legal accountability for alleged genocide against the Rohingya ethnic group of Myanmar under the 1948 Genocide Convention within the framework of international law. It adopts a normative juridical approach with qualitative legal analysis to assess the extent to which Myanmar’s authorities meet the legal elements of genocide under the Convention and the scope of state responsibility in preventing and punishing such crimes. Through doctrinal interpretation and comparative jurisprudence from the ICJ, ICTR, and ICTY, the study clarifies normative accountability mechanisms in contemporary genocide cases. The Rohingya crisis demonstrates systematic violations of fundamental human rights, including mass killings, forced displacement, and denial of citizenship, revealing structural persecution and potential genocidal intent. The study emphasizes that state responsibility for genocide is erga omnes, binding upon the entire international community, thus allowing other states to demand accountability even when not directly affected. The case brought by The Gambia against Myanmar before the International Court of Justice highlights the critical role of international judicial mechanisms in enforcing state obligations under the Genocide Convention. However, political barriers, particularly within the UN Security Council, often impede the effective implementation of international norms. The paper concludes that Myanmar’s conduct toward the Rohingya aligns with the elements of genocide as defined by international law and underscores the necessity of strengthening enforcement mechanisms to ensure justice and prevent future atrocities.